First record of a subterranean termite, Coptotermes havilandi Holmgren (Isoptera: Rhinotermitidae), on the West coast of North America (México) - Ferraz, Marisa Vianna; Méndez-Montiel, José Tulio (Instituto de Ecología, A.C., 2020)
The subterranean termite, Coptotermes havilandi Holmgren, is reported from a previously undocumented sitelocated in Manzanillo, Colima, Mexico. This is the first record of that exotic species on the West Coast of NorthAmerica. Termites were found inhabiting and damaging pine logs in a fiscal warehouse at Manzanillo harbor. Theirproximity to the harbor, in addition to the lack of any other infestations in the surroundings, suggests that they wereprobably introduced as a result of maritime trade. New distribution records are also reported in Mexico City(Mexico) and the State of Pará (Brazil). This study shows that that species continues being introduced in manycountries despite the efforts of harbor quarantines.